2008
DOI: 10.1007/s10347-008-0172-2
|View full text |Cite
|
Sign up to set email alerts
|

The bioeroded megasurface of Oura (Algarve, south Portugal): implications for the Neogene stratigraphy and tectonic evolution of southwest Iberia

Abstract: The use of rocky palaeoshore bioerosion analysis as a tool to solve stratigraphic and tectonic issues is beginning to bear fruits. The occurrence of an extensive intra-Miocene marine abrasion platform in southern Portugal at Oura (Albufeira) has been identiWed on the basis of bioerosion trace fossils analysis. The observed ichnodiversity is rather low, with bivalve boring Gastrochaenolites being dominant. Nevertheless, the ichnoassemblage may be assigned to the Entobia ichnofacies. The palaeoichnological study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Formation of a hardground is related to a fall in sea level (e.g., Bromley and Asgaard 1993;Ghibaudo et al 1996;MacEachern et al 2007b;Cachão et al 2009;Santos et al 2010). The Glossifungites ichnofacies has been recognized at the base of regressive deposits .…”
Section: Trypanites-balanoglossites Ichnoassociation (Ia 4)mentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of a hardground is related to a fall in sea level (e.g., Bromley and Asgaard 1993;Ghibaudo et al 1996;MacEachern et al 2007b;Cachão et al 2009;Santos et al 2010). The Glossifungites ichnofacies has been recognized at the base of regressive deposits .…”
Section: Trypanites-balanoglossites Ichnoassociation (Ia 4)mentioning
confidence: 99%
“…Gastrochaenolites is a generally shallow water trace fossil (Bromley and Asgaard 1993;Farinati and Zavala 2002;Cachão et al 2009;Santos et al 2010) although Bassi et al (2011) reported this ichnogenus from a deep water reef setting. Recently, Santos et al (2011) described this ichnospecies even from basalts.…”
Section: Archaeonassa Fossulatamentioning
confidence: 99%
“…Notice that in bed 3 (where they place the age from Boski et al 1995) we have obtained an isotopic age of 9.5 (+1.0/¡0.5) Ma (which was also referred to in Pais et al 2000, in the table of isotopic age data). Furthermore, we have obtained an isotopic age of 8.3 (+2.2/¡3.3) Ma, for bed 6 of Cachão et al (2009), which they do not make reference to. Notice again that in bed 12 of our section (coarse conglomerate with large oysters), which corresponds to bed 8 of Cachão et al (2009), they erroneously put the age that we obtained in the Olhos de Água section.…”
mentioning
confidence: 70%
“…A correspondence between our description and measured section (see Legoinha 2001, p. 177, Wg. 63) and the graphic columnar section of Cachão et al (2009) can easily be established. Notice that in bed 3 (where they place the age from Boski et al 1995) we have obtained an isotopic age of 9.5 (+1.0/¡0.5) Ma (which was also referred to in Pais et al 2000, in the table of isotopic age data).…”
mentioning
confidence: 99%
“…The present work illustrates new approaches to the study of trace fossils by incorporating reliable systematically acquired geometric data and its processing by means of appropriated spatial analysis operators. Due to its novelty relative to more traditional ichnological studies (e.g., Cachão et al 2009), field data acquisition procedures and statistical analysis are extensively described. Thus, for the present study, we selected data from one sector only of the overall bioeroded surface described in the following chapter.…”
Section: Introductionmentioning
confidence: 99%